The Role of Personal Resilience and Interpersonal Support in Building Fulfilling and Prosocial Lives: Examining the Good Lives Model among Young Women Four Years after Youth Detention - Van Damme, Lore (International journal of offender therapy and comparative criminology, 2022)
Despite growing interest in strength-based rehabilitation frameworks, relevant internal/external resources that are likely to facilitate the rehabilitation of detained female adolescents (DFA) have been understudied. This study aims to fill this gap by studying the role of young women’s personal resilience and interpersonal support in building fulfilling and prosocial lives 4 years after youth detention, thereby examining the strength-based good lives model (GLM). Forty-nine former DFA (Mage = 20.75) completed questionnaires about resilience, support, Quality of Life (QoL), and offending. Hierarchical multiple regression analyses showed that young women with more resilience displayed higher QoL and less offending, while more support was associated with higher QoL only. The relationship between resilience and QoL/offending did not depend upon the level of support. Overall, our results support the applicability of the GLM to former DFA, showing evidence for the importance of both internal and external resources in building fulfilling and prosocial lives.